2016
DOI: 10.1080/14787210.2016.1244481
|View full text |Cite
|
Sign up to set email alerts
|

Ceftobiprole medocaril (BAL-5788) for the treatment of complicated skin infections

Abstract: With resistance of S. aureus, the most prevalent identified pathogen in skin and soft tissue infections, on the rise, the need for safe, effective, and well-tolerated antibiotics is crucial. Ceftobiprole medocaril (BAL-5788), ceftobiprole's parenteral prodrug, is a bactericidal cephalosporin with broad Gram-positive and Gram-negative activity that has shown to be well-tolerated and noninferior to vancomycin and vancomycin plus ceftazidime in the treatment of MRSA complicated skin and skin structure infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a pivotal clinical trial assessing the efficacy of Zevtera in treating Staphylococcus aureus bloodstream infections 16,17 including right-sided infective endocarditis, the study demonstrated significant therapeutic benefits. The trial was a randomized, double-blind, multicenter study comparing ceftobiprole to standard therapy, typically involving vancomycin with or without an aminoglycoside.…”
Section: Staphylococcus Aureus Bloodstream Infections (Bacteremia)mentioning
confidence: 99%
“…In a pivotal clinical trial assessing the efficacy of Zevtera in treating Staphylococcus aureus bloodstream infections 16,17 including right-sided infective endocarditis, the study demonstrated significant therapeutic benefits. The trial was a randomized, double-blind, multicenter study comparing ceftobiprole to standard therapy, typically involving vancomycin with or without an aminoglycoside.…”
Section: Staphylococcus Aureus Bloodstream Infections (Bacteremia)mentioning
confidence: 99%
“…Ceftobiprole has broad-spectrum activity against Gram-positive pathogens, including resistant strains of streptococci and MRSA, and Gram-negative organisms, including Enterobacterales and ceftazidime-susceptible P. aeruginosa [46]. Ceftobiprole has the capacity to bind to penicillin binding protein (PBP) 2a and PBP2x, conferring activity against MRSA.…”
Section: Ceftobiprolementioning
confidence: 99%
“…However, ceftobiprole is currently approved in Canada and in 13 countries in Europe for treatment of adults with community-acquired and hospital-acquired pneumonia, with the exception of ventilator-associated pneumonia. Despite data coming from phase III trials supporting the use of ceftobiprole for the treatment of cSSTIs, the drug failed to gain approval for this indication from the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) so far [48].…”
Section: Ceftobiprolementioning
confidence: 99%